2001
DOI: 10.1021/ie000526s
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Equilibrium in the Isomerization of 2,4,4-Trimethyl Pentenes

Abstract: The isomerization reaction of 2,4,4-trimethyl-1-pentene to 2,4,4-trimethyl-2-pentene was studied. In contrast to the general rule for alkene stability, an excess of the R-alkene (2,4,4-trimethyl-1-pentene) was observed in the thermodynamic equilibrium. The result is explained in terms of the molecular structure: the large and bulky substituents in 2,4,4-trimethyl-2-pentene cause steric tension and make the molecule less stable. A reaction enthalpy of 3.51 ( 0.03 kJ mol -1 , i.e., endothermic reaction, and a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…Obtained results are presented in Table 8. Equilibrium constants from Table 8 are comparable to those reported in a specific study of the isomerization reaction between both trimethylpentenes, TMP-1 and TMP-2 (Karinen et al, 2001b). K x5 ranged from 0.242 to 0.286 and K 5 hardly changed in the temperature range from 1.018 to 1.019, which are very close to the unity, as expected, because only two similar olefins are involved in this reaction.…”
Section: T (K) This Work Franç Oisse Andsupporting
confidence: 84%
See 3 more Smart Citations
“…Obtained results are presented in Table 8. Equilibrium constants from Table 8 are comparable to those reported in a specific study of the isomerization reaction between both trimethylpentenes, TMP-1 and TMP-2 (Karinen et al, 2001b). K x5 ranged from 0.242 to 0.286 and K 5 hardly changed in the temperature range from 1.018 to 1.019, which are very close to the unity, as expected, because only two similar olefins are involved in this reaction.…”
Section: T (K) This Work Franç Oisse Andsupporting
confidence: 84%
“…Slightly different values were found by Karinen et al (2001b), who reported experimental values of 3.51 kJ/mol for r H Besides, Turner et al (1958) published an experimental value of 5.4 kJ/mol for the enthalpy change of reaction, nearby the same value obtained in this work. The similarity between results and the good fit obtained from experimental data for this isomerization reaction between trimethylpentenes enforces the reliability of the present study.…”
Section: T (K) This Work Franç Oisse Andsupporting
confidence: 71%
See 2 more Smart Citations
“…In addition, isomerization between both diisobutenes (R10) also took place, the formation of TMP-1 being favored, since TMP-1 is a more stable molecule than TMP-2 due to the internal repulsions caused by the large size of the tert-butyl group in the TMP-2 molecule [47,48]. As observed in Figure 9a, when C4 dimers were forms, the TMP-1/TMP-2 molar ratio was around 4 at the end of runs, consistent with published results [47] and with the thermodynamic equilibrium constant for trimethylpentenes isomerization (R10), which are in the range from 0.26 to 0.29 for the assayed temperatures [31]. From IA dimerization (R12 in Figure 1), a wide variety of diisoamylenes can be formed [49].…”
Section: Dimers and Codimers Formationmentioning
confidence: 99%